Cyclobotryoxide, a phytotoxic metabolite produced by the plurivorous pathogen Neofusicoccum australe. - Andolfi, Anna; Maddau, Lucia; Cimmino, Alessio; Linaldeddu, Benedetto T.; Franceschini, Antonio; Serra, Salvatorica; Basso, Sara; Melck, Dominique; Evidente, Antonio (Journal of natural products, 2012)
Two isolates of Neofusicoccum australe belonging to ITS haplotypes H4 and H1 and associated with grapevine cordon dieback and branch dieback of Phoenicean juniper, respectively, have been shown to produce in vitro structurally different secondary metabolites. From the strain BOT48 of N. australe (haplotype H4) a new cyclohexenone oxide, namely, cyclobotryoxide, was isolated together with 3-methylcatechol and tyrosol. Cyclobotryoxide was characterized as (1S,5R,6S)-5-hydroxy-3-methoxy-4-methyl-7-oxabicyclo[4.1.0]hept-3-en-2-one by spectroscopic, optical, and chemical methods. The strain BL24 (haplotype H1) produced tyrosol along with botryosphaerone D and (3S,4S)-3,4,8-trihydroxy-6-methoxy-3,4-dihydro-1(2H)-naphthalenone. The metabolites obtained from both strains were tested at four concentrations on leaves of grapevine cv. Cannonau, holm oak, and cork oak by the leaf puncture assay. Cyclobotryoxide proved to be the most phytotoxic compound. Tyrosol and cyclobotryoxide were also tested on detached grapevine leaves at concentrations of 0.25 and 0.5 mg/mL. Only cyclobotryoxide was found to be active in this bioassay.
The following values have no corresponding Zotero field: accession-num: 23046443
Keywords: Ascomycota; Ascomycota: chemistry; Bicyclo Compounds, Heterocyclic; Bicyclo Compounds, Heterocyclic: chemistry; Bicyclo Compounds, Heterocyclic: isolation & purif; Bicyclo Compounds, Heterocyclic: pharmacology; Catechols; Cyclohexanones; Cyclohexanones: chemistry; Cyclohexanones: isolation & purification; Cyclohexanones: pharmacology; Juniperus; Juniperus: microbiology; Molecular Structure; mycotoxins; Mycotoxins: chemistry; Mycotoxins: isolation & purification; Mycotoxins: pharmacology; Nuclear Magnetic Resonance, Biomolecular; Quercus; Quercus: drug effects; Stereoisomerism; Vitis; Vitis: drug effects

Linear Aliphatic Dimeric Esters from Cork Suberin - Graça, José; Santos, Sara (Biomacromolecules, 2006)
Cork suberin was partially depolymerized by methanolysis catalyzed by calcium hydroxide. Analysis by GC-MS of the methanolysate showed suberin monomers, including glycerol and long-chain α,?-diacids and ?-hydroxyacids. ESI-MS analysis of the methanolysate showed, besides the aliphatic monomers, suberin oligomers, including linear dimeric esters of α,?-diacids and ?-hydroxyacids. Two types of dimeric esters were identified:? a α,?-diacid linked to a ?-hydroxyacid and two inter-linked ?-hydroxyacids. The α,?-diacids and ?-hydroxyacids found as monomer residues in the dimeric esters were mainly the C18 monomers with midchain substituents. The identification of these dimeric esters was based in their CID-MS/MS spectra and confirmed after synthesis of model compounds. The occurrence of inter-esterified long-chain monomers in suberin brings a new insight in the understanding of the polyester structure of this biopolymer.
From Duplicate 1 (Linear Aliphatic Dimeric Esters from Cork Suberin - Graça, José; Santos, Sara)
Keywords: cork suberin; dimeric esters; Dimerization; Electrospray Ionization; Electrospray Ionization: metho; Esters; Esters: chemistry; GC-MS (voyant); Lipids; Mass; Membrane Lipids; Membrane Lipids: chemistry; Molecular Structure; Sensitivity and Specificity; Spectrometry; Trees; Trees: chemistry

Assignment of the Absolute Configuration of (+)-Diplopyrone, the Main Phytotoxin Produced by Diplodia mutila, the Pathogen of the Cork Oak Decline, by a Nonempirical Analysis of Its Chiroptical Properties† - Giorgio, Egidio; Maddau, Lucia; Spanu, Emanuela; Evidente, Antonio; Rosini, Carlo (The Journal of Organic Chemistry, 2004)
The nonempirical assignment of the absolute configuration of (+)-diplopyrone, the main phytotoxin of Diplodia mutila, i.e., an endophytic fungus, widespread in Sardinian oak forests, and considered one of the main causes of cork oak decline, has been approached by two different methods:? (a) the exciton analysis of the circular dichroism (CD) spectrum and (b) the ab initio calculation of the optical rotatory power. Both methods indicate that (+)-diplopyrone is 6-[(1S)-1-hydroxyethyl]-2,4a(S),6(R),8a(S)-tetrahydropyrano[3,2-b]pyran-2-one, so the stereostructure of this important biomolecule is safely determined for the first time. A comparison of advantages and limitations of the two methods of analysis is also presented.
From Duplicate 2 (Assignment of the Absolute Configuration of (+)-Diplopyrone, the Main Phytotoxin Produced by Diplodia mutila, the Pathogen of the Cork Oak Decline, by a Nonempirical Analysis of Its Chiroptical Properties† - Giorgio, Egidio; Maddau, Lucia; Spanu, Emanuela; Evidente, Antonio; Rosini, Carlo)
Keywords: absolute configuration; Circular dichroism; DeVoe method; diplopyrone (voyant); Mitosporic Fungi; Mitosporic Fungi: pathogenicity; Models; Molecular; Molecular Structure; mycotoxins; Mycotoxins: chemistry; Optical rotation; Plant Diseases; Plant Diseases: microbiology; Pyrones; Pyrones: chemistry; Stereoisomerism